Participatory Development Approach for the Rural Road Networks: A Case of Infrastructure Development Office, Kaski - Tiwari, Rabindra (Academia Journal of Humanities & Social Sciences, 2024)
This study aims to assess people’s participation in the rural road projects in Kaski District of Gandaki Province. The data were collected from 50 conveniently selected residents along the road project alignment Dopahare-Kristi-Bakrek- Pawaigaude area, using the convenient sampling procedure. This study is descriptive, and the questionnaires were used to collect data concerning the people’s participation and road infrastructure development in the villages. The findings of the study reveal that the presence of poor rural road infrastructure, both in quality and access, the road sector was found external resource-dependent, deficient in resource mobilization and topography of the rural area by itself escalates the problem. The community participation is not well-institutionalized in this project. The study concludes that public participation is crucial in developing a country like Nepal. People’s participation in Nepal is limited only for elite people, but not for people from disadvantaged groups. Though people’s participation has increased in Nepal over the last few decades but people from the underprivileged groups do not participate to the same extent of the elite group, which creates disputes in the society. This study recommends all concerned bodies such as the local communities, the municipality, and other stakeholders to take their responsibility to solve this critical issue.